Self-testing for pregnancy: a systematic review and meta-analysis - Ping Teresa Yeh; Caitlin E Kennedy; Manjulaa Narasimhan; Karima Gholbzouri (BMJ Open)
Objectives Urine pregnancy tests are often inaccessible in low-income settings. Expanded provision of home pregnancy testing could support self-care options for sexual and reproductive health and rights. We conducted a systematic review of pregnancy self-testing effectiveness, values and preferences and cost.Design Systematic review and meta-analysis using the Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) approach.Data sources PubMed, CINAHL, LILACS and EMBASE and four trial registries were searched through 2 November 2020.Eligibility criteria for selecting studies We included trials and observational studies that compared urine self-testing for pregnancy to health worker-led pregnancy testing on effectiveness outcomes; quantitative and qualitative studies describing values and preferences of end users and health workers and costs of pregnancy self-testing.Data extraction and synthesis Two independent reviewers used standardised methods to search, screen and code included studies. Risk of bias was assessed using the Cochrane Collaboration and Evidence Project tools. Meta-analysis was conducted using random effects models. Findings were summarised in GRADE evidence profiles and synthesised qualitatively.Results For effectiveness, four randomised trials following 5493 individuals after medical abortion showed no difference or improvements in loss to follow-up with home pregnancy self-testing compared with return clinic visits. One additional trial of community health workers offering home pregnancy tests showed a significant increase in pregnancy knowledge and antenatal counselling among 506 clients. Eighteen diverse values and preferences studies found support for pregnancy self-testing because of quick results, convenience, confidentiality/privacy, cost and accuracy. Most individuals receiving pregnancy self-tests for postabortion home management preferred this option. No studies reported cost data.Conclusion Pregnancy self-testing is acceptable and valued by end users. Effectiveness data come mostly from articles on postabortion care, and cost data are lacking. Greater availability of pregnancy self-tests, including in postabortion care and CHW programs, may lead to improved health outcomes.PROSPERO registration number CRD42021231656.